Phenotypic Features of Circulating Leukocytes from Non-human Primates Naturally Infected with Trypanosoma cruzi Resemble the Major Immunological Findings Observed in Human Chagas Disease. - Renato Sathler-Avelar; Danielle Marquete Vitelli-Avelar; Armanda Moreira Mattoso-Barbosa; Marcelo Perdigão-; Ronaldo Peres Costa; Silvana Maria Elói-Santos; Matheus de Souza Gomes; Laurence Rodrigues do Amaral; Andréa Teixeira-Carvalho; Olindo Assis Martins-Filho; Edward J Dick; Gene B Hubbard; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Cynomolgus macaques (Macaca fascicularis) represent a feasible model for research on Chagas disease since natural T. cruzi infection in these primates leads to clinical outcomes similar to those observed in humans. However, it is still unknown whether these clinical similarities are accompanied by equivalent immunological characteristics in the two species. We have performed a detailed immunophenotypic analysis of circulating leukocytes together with systems biology approaches from 15 cynomolgus macaques naturally infected with T. cruzi (CH) presenting the chronic phase of Chagas disease to identify biomarkers that might be useful for clinical investigations. METHODS AND FINDINGS:Our data established that CH displayed increased expression of CD32+ and CD56+ in monocytes and enhanced frequency of NK Granzyme A+ cells as compared to non-infected controls (NI). Moreover, higher expression of CD54 and HLA-DR by T-cells, especially within the CD8+ subset, was the hallmark of CH. A high level of expression of Granzyme A and Perforin underscored the enhanced cytotoxicity-linked pattern of CD8+ T-lymphocytes from CH. Increased frequency of B-cells with up-regulated expression of Fc-γRII was also observed in CH. Complex and imbricate biomarker networks demonstrated that CH showed a shift towards cross-talk among cells of the adaptive immune system. Systems biology analysis further established monocytes and NK-cell phenotypes and the T-cell activation status, along with the Granzyme A expression by CD8+ T-cells, as the most reliable biomarkers of potential use for clinical applications. CONCLUSIONS:Altogether, these findings demonstrated that the similarities in phenotypic features of circulating leukocytes observed in cynomolgus macaques and humans infected with T. cruzi further supports the use of these monkeys in preclinical toxicology and pharmacology studies applied to development and testing of new drugs for Chagas disease.